Efficacy and safety of percutaneous cryoablation for elderly patients with small hepatocellular carcinoma: A prospective multicenter study. (6th February 2022) - Luo, Jing; Dong, Zheng; Xie, Hui; Zhang, Wei; An, Linjing; Yu, Zhe; Chang, Xiujuan; Chen, Yan; Yang, Wuwei; Hu, Kaiwen; Liu, Fuquan; Yang, Yongping
Abstract: Background & Aims: Management of elderly patients with hepatocellular carcinoma (HCC) has become a major concern. Some data suggest that cryoablation improves the outcomes of elderly patients with HCC, but its efficacy and safety remain unknown. This study aimed to evaluate and compare the efficacy and safety of percutaneous cryoablation with those of radiofrequency ablation (RFA) for elderly HCC patients. Methods: In all, 223 patients with small HCC aged ≥70 years, treatment‐naïve, without metastasis were enrolled and randomized into a cryoablation group (n = 112) or a RFA (n = 111) group from July 2015 to October 2018. The primary endpoint was local tumour progression (LTP) at 3 years after treatment. The secondary endpoints including overall survival (OS), tumour‐free survival (TFS), LTP and safety were analysed for these two groups after both treatments. Results: LTP rates at 1‐, 3‐ and 5‐year were 12%, 17% and 20% for cryoablation and 17%, 18% and 21% for RFA respectively ( P = .735). For lesions >3 cm in diameter, LTP rates at 1‐ and 3‐year were 13% and 22% in cryoablation group and 22% and 42% respectively, in the RFA group ( P = .039). The 1‐, 3‐ and 5‐year OS rates were 90, 75% and 62% for cryoablation and 90%, 68% and 63% for RFA respectively ( P = .331). The 1‐, 3‐ and 5‐year TFS rates were 59%, 32% and 25% in the cryoablation and 59%, 28% and 20% in the RFA respectively ( P = .309). Major complications occurred in 6 patients (5%) following cryoablation and 6 patients (6%) following RFA ( P = .886). Conclusion: Cryoablation and RFA had similar LTP in elderly patients with small HCC and this study failed to meet the primary endpoint, although for a relatively large early‐stage HCC the LTP rate after cryoablation was significantly lower than that after RFA.